2012
DOI: 10.2340/00015555-1220
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Maturation of Skin Dendritic Cell Subsets in Two Forms of Cutaneous T-Cell Lymphoma: Mycosis Fungoides and Sézary Syndrome

Abstract: Dendritic cells (DCs) critically regulate immune responses and the "immune-surveillance" of tumours. This study retrospectively analysed the distribution and maturation status of DC-subsets in T-cell lymphoma of the skin. Mycosis fungoides and Sézary syndrome (n = 25) were investigated immunohistochemically for DC subsets, based on C-type lectin receptor expression: Langerhans' cells (langerin/CD207+, DEC-205/CD205+), dermal DCs (DC-SIGN/CD209+, CD205+) and plasmacytoid DC (BDCA-2/CD303+). Maturation status wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 36 publications
(37 reference statements)
2
20
1
7
Order By: Relevance
“…The other type showed a much more dendritic shape. 22 In our case, the unidentified cells did not display the features of two opposite aspects of plasmacytoid DCs. In addition, frozen immunohistochemistry, flow cytometry or immunoflurescence techniques are not possible because no cryomaterial was available (as our case presented by solitary small nodule) to perform wide panel of markers.…”
Section: Discussioncontrasting
confidence: 44%
“…The other type showed a much more dendritic shape. 22 In our case, the unidentified cells did not display the features of two opposite aspects of plasmacytoid DCs. In addition, frozen immunohistochemistry, flow cytometry or immunoflurescence techniques are not possible because no cryomaterial was available (as our case presented by solitary small nodule) to perform wide panel of markers.…”
Section: Discussioncontrasting
confidence: 44%
“…DC-SIGN is expressed at sites in the skin (dermis) where T. rubrum is known to enter the host. Therefore, DC-SIGN-positive DCs might, trough these C-type lectin receptors, form the first encounter with these pathogens and the host immune system and, after antigen presentation, initiate a cellular response [21] [22] [23]. The results also shown that others receptors could participate in the bind of T.rubrum with macrophages or dendritic cells.…”
Section: Discussionmentioning
confidence: 82%
“…2). The number of mDCs, pDCs, and CD163 + macrophages has been reported to increase in MF (19, 20). Though their roles in MF remain to be elucidated, the involvement of mDCs, pDCs and macrophages in other malignancies is well established (21).…”
Section: Discussionmentioning
confidence: 99%